Identification of Feeder Vessels in Ocular Surface Neoplasia Using Indocyanine Green Angiography: A Preliminary Report. (1st February 2018) - Brunner, Matthias; Steger, Bernhard; Romano, Vito; Hodson, Martin; Zheng, Yalin; Heimann, Heinrich; Kaye, Stephen B
ABSTRACT: Purpose : To evaluate indocyanine green angiography (ICGA) for the identification and characterization of afferent (feeding) and efferent (draining) vessels in patients with ocular surface neoplasia. Materials and Methods : Consecutive patients with biopsy-proven benign, pre-invasive, or invasive ocular surface tumors of the bulbar conjunctiva were included. Patients underwent anterior segment optical coherence tomography, ICGA, and color photography for the evaluation of the thickness, location, number, and diameter of afferent and efferent vessels of the lesions. Results : Twenty-two eyes of 22 patients with papillomas ( n = 4), intra-epithelial neoplasia lesion ( n = 2) in situ or invasive carcinomas ( n = 6), nevus ( n = 5), conjunctival melanocytic intra-epithelial neoplasia lesion ( n = 1), and in situ or invasive melanomas ( n = 4) were investigated. Afferent (feeder) vessels were identified in all lesions. There were fewer afferent (3.1 ± 1.6) than efferent (7.5 ± 3.5) vessels per lesion ( p < 0.001) and the mean diameter was smaller for afferent (101 ± 62 μm, 28–281) than efferent vessels (137 ± 51 μm, 31–652; p = 0.017). The number of afferent and efferent vessels was associated with the thickness of the lesion ( p = 0.037, p < 0.01). Lesion filling times differed between benign and invasive or pre-invasive lesions ( p = 0.018). Conclusions : ICGA is a useful adjunctive in vivo imaging method for the assessment of the vasculature in patients with suspected ocular surface neoplasia.